SUBJECTIVE WELL BEING MANTAN PECANDU NARKOBA (SABU-SABU) - Panjaitan, Nadya Rotna Aprilian; Rudangta Arianti (Jurnal Cakrawala Ilmiah, 2024)
Subjective well-being is described as a form of subjective welfare evaluation derived from an individual's perception of their life, encompassing life satisfaction and pleasant or unpleasant feelings experienced in their life. This qualitative research, using a phenomenological approach, focuses on depicting subjective well-being and the factors influencing it in former drug addicts, particularly methamphetamine users. The study involved four adult participants. The results from four participants showed different portrayals of subjective well-being after quitting drugs. Although all participants still experienced and were dominated by feelings and thoughts that were not entirely positive, on the other hand, after undergoing rehabilitation and completely abstaining from drugs, the four participants were able to bring about changes in their way of thinking and viewing life, both cognitively and in their subjective experiences of life. Meanwhile, in the domain-specific satisfaction of the four participants, the results showed more variation. Additionally, this study also revealed key factors influencing subjective well-being, including social support, changes in mindset, and personal commitment from each individual. The implications of this research contribute to the development of clinical psychology, particularly regarding the description of subjective well-being in former drug addicts (methamphetamine users) and the factors influencing it.